2004
DOI: 10.2151/jmsj.82.1629
|View full text |Cite
|
Sign up to set email alerts
|

Regional Climate Simulation for Korea using Dynamic Downscaling and Statistical Adjustment

Abstract: Recently the regional impact assessment due to global warming is one of the urgent tasks to every country in the world, under the circumstances of increasing carbon dioxide in the atmosphere. This assessment must include not only meteorological factors, such as surface air temperature and precipitation, etc., but also the response of the local ecosystem. Based on a previous study, for example, it has been known that Phyllostachys' habitation, which is one of the bamboo species popular in Korea, is quite sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
0
26
0
1
Order By: Relevance
“…The horizontal resolution of HOPE-G corresponds to a Gaussian T42 grid (@2.8 ) and the model employs 20 vertical levels (Min et al 2005). Analysis of results using the ECHO-G scenario (Oh et al 2004) showed that the A2 [B2] scenarios over East Asia (defined as grid box of 80 E-180 E, and 20 N-60 N) by 2100 result in an increase in temperature of 6.5 [4.5] K and an increase in precipitation of 10.5 [6.0]%, respectively.…”
Section: Model and Experiments Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The horizontal resolution of HOPE-G corresponds to a Gaussian T42 grid (@2.8 ) and the model employs 20 vertical levels (Min et al 2005). Analysis of results using the ECHO-G scenario (Oh et al 2004) showed that the A2 [B2] scenarios over East Asia (defined as grid box of 80 E-180 E, and 20 N-60 N) by 2100 result in an increase in temperature of 6.5 [4.5] K and an increase in precipitation of 10.5 [6.0]%, respectively.…”
Section: Model and Experiments Designmentioning
confidence: 99%
“…The climate of Korea also has experienced a gradual warming (Oh et al 2004), as indicated by a significant warming trend from the observed record. In South Korea, the increasing rate of the average temperature is reported to be about 1.5 K during the 20th century mainly due to the greenhouse effect and rapid urbanization (Kwon 2005), which is almost three times of global warming trend.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Korea, concerning climate change modeling, several studies have been done using the MM5 and RegCM3 regional models along with ECHO-G GCM model outputs for Special Report on Emission Scenarios (SRES) A2 scenario (e.g., METRI, 2004;Oh et al, 2004;Im et al, 2007). Chang et al (2007) studied the vulnerability of Korean water resources to climate change and Bae et al (2008) studied potential changes in Korean water resources.…”
Section: Introductionmentioning
confidence: 99%